2018
DOI: 10.3390/su10113880
|View full text |Cite
|
Sign up to set email alerts
|

How Physical Environment Impacts Visitors’ Behavior in Learning-Based Tourism—The Example of Technology Museum

Abstract: Visiting a museum is a popular activity in the tourism industry, especially in cultural and learning-based tourism. To help plan museums effectively, this study investigated the underlying motivations and constraints and their impact on the perceived physical environment and visitor satisfaction toward a museum. The results suggest that the physical environment of museums serves as an axial mediator among motivations, constraints and visitor satisfaction. Six essential factors of physical environment are affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 109 publications
0
2
0
2
Order By: Relevance
“…Upgrading and updating various service facilities can create a good visiting environment [54]. Lighting and color are two important factors that influence the design effect of museum displays [7,[64][65][66]. Light not only improves the brightness of a room, but also combines the colors of the exhibits.…”
Section: Discussionmentioning
confidence: 99%
“…Upgrading and updating various service facilities can create a good visiting environment [54]. Lighting and color are two important factors that influence the design effect of museum displays [7,[64][65][66]. Light not only improves the brightness of a room, but also combines the colors of the exhibits.…”
Section: Discussionmentioning
confidence: 99%
“…The indoor design features in a museum contribute to shaping visitors' satisfaction [46]. Furthermore, Zhang et al [47] identified six essential factors in the physical environment influencing visitor satisfaction: architectural planning, exhibition and marketing, external environment and accessibility, entrance and ticketing, site planning, and shops and cafes.…”
Section: Functional Performance Elements In Museumsmentioning
confidence: 99%
“…Por su parte, el ambiente está integrado por los elementos naturales y artificiales que hacen posible la existencia y el desarrollo de un espacio. Por lo tanto, el ambiente dentro de un museo se conforma por los aspectos de atmósfera, seguridad de las instalaciones, incluso por la accesibilidad al público (Koukoulis et al, 2022;Zhang et al, 2018).…”
Section: Tic Y Servicio De Los Museosunclassified
“…En este sentido, el uso de las tIC está estrechamente ligado con la eficiencia del servicio proporcionado por parte de los agentes museográficos, debido a que mediante su uso aumentan tanto la eficiencia como la eficacia y se cumplen las expectativas del usuario (Lee et al, 2020). Así mismo, el servicio debe ser complementado por el ambiente, el cual debe contar con los instrumentos necesarios para brindar calidad (Komarac et al, 2017;Poll, 2018;Su & Teng, 2018;Zhang et al, 2018). Con base en esto, se postula la siguiente hipótesis: H 3 .…”
Section: Tic Y Servicio De Los Museosunclassified